Production of second generation. Bioethanol-effect of various pre-treatments on non-wood biomass towards sugar production. - Ieh , Cheu Peng (Universiti Sains Malaysia, 2016)

(untitled)
Water,acid and alkaline pretreatments prior to enzymatic hydrolysis of the three fibres for sugar production were optimized in this study. Response Surface Methodology was applied to statistically analyze and optimize pretreatments conditions based on total glucose yield as response variable.